Kemerdekaan dalam Puisi Ahmad Syauqi “Yā Ayyuhā Al-Sāil Mā Al-Ḥurriyyah” (Analisis New Historisisme) / Independence in Ahmad Syauqi's Poetry "Yā Ayyuhā As-Sāil Mā Al-Ḥurriyyah" (New Historism Analysis) - Ariyanti Rifa Nurhasanah; Yoyo Yoyo; Norfaezah Mohd Hamidin (Diwan : Jurnal Bahasa dan Sastra Arab, 2021)
يهدف هذا البحث إلى دراسة مفهوم الحريّة عند أحمد شوقي في قصيدته المعنونة بعنوان يا أيها السائل ما الحرية، باستخدام النظرية التاريخية الجديدة لستيفن غرينبلات (Stephen Greenblatt)، والكشف عن الخلفية التاريخية للاستعمار المصري وصلته بشعر أحمد شوقي، مما أدى إلى ظهور مفهوم معنى الاستقلال المرتبط بأحداث مصر التي حدثت في ذلك الوقت. الطريقة المستخدمة هي الطريقة الوصفية، وجمع بيانات هذا البحث، من خلال العملية التالية: ١) قراءة النص بشكل متكرر، ٢) ترجمة نص شعري، ٣) تسجيل جمل متعلقة بالأشياء الشكلية، ٤) تصنيف البيانات على أساس الأهداف. ويكون تحليل بيانات البحث من خلال المراحل التالية: ١) قراءة النص بالتوازي، ٢) عرض البيانات والمناقشة، ٣) عرض النتائج من نتائج التحليل. تظهر نتائج البحث حول مفهوم الحرية في شعر يآ أيها السائل ما الحرية: أولاً، تتأثر خصائص كتابة الشعر وأعمالها بالخلفية التاريخية التي عاشها المؤلف. ثانيًا، يمكن تحديد الظروف الاجتماعية والاقتصادية والسياسية للأمة في الأعمال الأدبية من خلال عملية الدراسة التاريخية الجديدة. ثالثًا، هناك ثلاثة مفاهيم لمعنى الحرية عند أحمد شوقي في قصيدة يآ أيها السائل ما الحرية، وهي: ١) الحريّة كشيء قيم ومقدس، ٢) الحريّة كمصدر للقوة الوطنية ، ٣) الحريّة كشكل من أشكال التضحية. الكلمات المفتاحية : الاستقلال؛ شعر أحمد شوقي؛ النظرية التاريخية الجديدة؛ الاستعمار.Abstract:This research aims to examine the independence concept in Ahmad Syauqi’s poetry entitled Yā Ayyuhā As-Sāil mā Al-Ḥuriyyah based on the theory of New Historicism by Stephen Greenblatt. This research tried to reveal the historical background of Egyptian colonialism and its relevance to Ahmad Syauqi's poetry, thus giving the meaning concept of independence a meaning related to the events at the time. Formally, the independence concept is coupled with the theory of New Historicism. The method used is descriptive-qualitative, collecting research data through the following process; 1) reading the text repeatedly, 2) translating the poetry text, 3) recording sentences related to formal objects, and 4) classifying the data based on the purpose. Meanwhile, research data analysis was carried out through the following stages; 1) reading the text in parallel, 2) presenting data and discussion, and 3) presenting conclusions from the results of the analysis. The results of the study on the concept of independence in the poem Yā Ayyuhā As-sāil Mā Al-ḥuriyyah showed that the characteristics and works of poetry are influenced by the historical background experienced by the author. Secondly, a nation's social, economic, and political conditions can be identified in literary works through the New Historicism study process. Thirdly, there are three concepts of the meaning of independence based on Ahmad Syauqi’s poetry, ‘Yā Ayyuhā As-sāil Mā Al-ḥuriyyah’, namely: 1) independence as something precious and sacred, 2) independence as a source of national strength, and 3) independence as a form of sacrifice.